ALGORITMA K-MEANS DALAM PENGELOMPOKAN SURAT KELUAR DI KANTOR KEMENTERIAN AGAMA KOTA PEMATANG SIANTAR - Nasution, Mhd Aditia; Safii, M. (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2024)
The management of outgoing letters within the Office of the Ministry of Religious Affairs in Pematang Siantar City is a crucial aspect of its operations. In an effort to enhance the efficiency and effectiveness of outgoing letter management, this research introduces the implementation of the K-Means Algorithm as one of the solutions. The objective of this research is to evaluate the impact of using the K-Means Algorithm in grouping outgoing letters. The results of the research indicate that the K-Means Algorithm has significantly aided in the process of grouping outgoing letters by identifying relevant patterns and characteristics. Grouping outgoing letters based on specific attribute similarities has allowed for improved letter distribution efficiency and a better understanding of sending patterns. Furthermore, the potential for further development in terms of integration with an electronic letter management system is evident. Therefore, this research demonstrates that the K-Means Algorithm has the potential to enhance outgoing letter management within the Office of the Ministry of Religious Affairs in Pematang Siantar City and can be considered a valuable tool in improving operational efficiency and publicservice.